Analysis of factors potentially associated with nursing students' academic outcomes: A thirteen-year retrospective multi-cohort study. (November 2018) - Lancia, L.; Caponnetto, V.; Dante, A.; Mattei, A.; La Cerra, C.; Cifone, M.G.; Petrucci, C.
Abstract: Background: Low academic success rates lead to fewer than the required number of nurses entering the national health systems, impacting on the supply of nurses and with negative consequences for global health care since low nurse-to-patient ratios are associated with an increase of patients' adverse outcomes. Objectives: This study was mainly aimed at documenting any of the academic outcomes' potential predictors among Nursing Degree Program (NDP) students' characteristics. Design: A retrospective multi-cohort study was conducted. Participants and Setting: Ten cohorts of nursing students enrolled in a central Italy university were involved. Methods: Qualitative and quantitative data on entry characteristics and academic outcomes were retrieved, observing retrospectively 10 cohorts of Italian nursing students for 13 academic years (2004–2017). Multiple regression analyses were conducted to assess if potential predictors reporting a p-value < 0.05 in univariate analyses were independently related to academic outcomes. Results: A total of 2278 students were enrolled in this study. Multivariate analyses showed that 'female gender', 'having attended classical or scientific upper-secondary school', and 'having higher upper-secondary diploma grade' were associated both with the qualitative outcomes (graduation within the legal duration of NDP) and the quantitative ones (final degree exam grade). The weight of the 'admission-test score' in explaining the variance of academic performances was very low ( β  = 0.03, 95% CI = 0.01 to 0.05) compared to the 'upper-secondary diploma grade' ( β  = 0.14, 95% CI = 0.12 to 0.16). Conclusions: This evidence should lead to a reflection on the entry-selection methods for NDP, especially in those countries such as Italy, where these methods are essentially based on the entry-test, which in this study was shown to have a very low predictive power for academic outcomes.